2011
DOI: 10.1177/1065912911424288
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Political Institutions? Constitutional Choice in Postindependence Francophone Sub-Saharan Africa

Abstract: The study of the effects of institutions suffers from a potential endogeneity problem. This article proposes a strategy for addressing this problem by estimating the motivations for institutional choice directly. It identifies the motivations behind the wording of post-independence constitutions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…28 With regard to Francophone Africa, Elgie finds "a mix of endogenous and exogenous preferences" in constitutional choices. 29 Although he had no special interest in constitutional courts, Elgie's quantitative analysis provides sound initial evidence for the combination of diffusion and insurance elements into one theoretical approach.…”
Section: Integrating Two Theories: Diffusion and Strategic Actionmentioning
confidence: 99%
“…28 With regard to Francophone Africa, Elgie finds "a mix of endogenous and exogenous preferences" in constitutional choices. 29 Although he had no special interest in constitutional courts, Elgie's quantitative analysis provides sound initial evidence for the combination of diffusion and insurance elements into one theoretical approach.…”
Section: Integrating Two Theories: Diffusion and Strategic Actionmentioning
confidence: 99%
“…When using an IV, this study found that autocratic regimes in countries colonised by France or Portugal or former communist bloc countries tended to choose semi-presidentialism, and once adopting that, they were more likely to become HPRs (see Model 1 and 2). However, there is an institutional variation within former French colonies determined by their strength of ties with France (Elgie, 2012). Using colonial legacies from France as an instrument was, therefore, too arbitrary.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we find little overall support for the idea that the French were better at implanting their institutions in places that were more valuable (in terms of exports) to France or in places that had more French people per capita. The lack of support for this last explanation is surprising, as post-independence ties to France have been shown to have influenced the wording of constitutions in French West Africa (Elgie 2012).…”
Section: Resultsmentioning
confidence: 99%